The Influence Of Islamic Income And Financial Literacy On The Decision To Finance In Islamic Banks - saparuddin saparuddin; Windari windari; azwar hamid; ananda anugrah (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The results of the initial survey of traders in Panyabungan District as many as 37 out of 50 chose credit from conventional banks over financing in Islamic banks. The decrease in people's income levels drastically due to coronavirus disease, resulting in lowering people's purchasing power so that it will affect the income of traders.The low Islamic financial literacy that occurs in the community, which is only 8.93%, is far below the national financial literacy of 38.03%. The formulation of the problem in this study is whether income has an effect on traders' decisions to finance at Islamic banks in Panyabungan District? Does Islamic financial literacy affect traders' decisions to finance at Islamic banks in Panyabungan District? Do income and Islamic financial literacy simultaneously affect the decision of traders to do financing at Islamic banks in Panyabungan District?. This research is quantitative research.The sample in this study amounted to 70 respondents using the incidental sampling technique. The data analysis techniques used are validity test, reliability test, descriptive statistical analysis test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t-test, and F test. The results of the study used the t-test of income with –ttable ≤ tcount ≤ ttable (-1.66792 ≤ - 1.304 ≤ 1.66792) with sig. 0.197 0.1, it can be concluded that income has no effect on the decision of traders to finance at Islamic banks in Panyabungan District, Islamic financial literacy with tcount ttable (3.646 1.66792) with a sign. 0.001 0.1, it can be concluded that Islamic financial literacy affects the decision of traders to finance at Islamic banks in Panyabungan District. The results of the F test show that Fcount is 7.232 Ftable is 2.38 with a sign. 0.001 0.1, so it can be concluded that income and Islamic financial literacy simultaneously affect the decision of traders to finance at Islamic banks in Panyabungan District.The results of the initial survey of traders in Panyabungan District as many as 37 out of 50 chose credit from conventional banks over financing in Islamic banks. The decrease in people's income levels drastically due to coronavirus disease, resulting in lowering people's purchasing power so that it will affect the income of traders.The low Islamic financial literacy that occurs in the community, which is only 8.93%, is far below the national financial literacy of 38.03%. The formulation of the problem in this study is whether income has an effect on traders' decisions to finance at Islamic banks in Panyabungan District? Does Islamic financial literacy affect traders' decisions to finance at Islamic banks in Panyabungan District? Do income and Islamic financial literacy simultaneously affect the decision of traders to do financing at Islamic banks in Panyabungan District?. This research is quantitative research.The sample in this study amounted to 70 respondents using the incidental sampling technique. The data analysis techniques used are validity test, reliability test, descriptive statistical analysis test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t-test, and F test. The results of the study used the t-test of income with –ttable ≤ tcount ≤ ttable (-1.66792 ≤ - 1.304 ≤ 1.66792) with sig. 0.197 0.1, it can be concluded that income has no effect on the decision of traders to finance at Islamic banks in Panyabungan District, Islamic financial literacy with tcount ttable (3.646 1.66792) with a sign. 0.001 0.1, it can be concluded that Islamic financial literacy affects the decision of traders to finance at Islamic banks in Panyabungan District. The results of the F test show that Fcount is 7.232 Ftable is 2.38 with a sign. 0.001 0.1, so it can be concluded that income and Islamic financial literacy simultaneously affect the decision of traders to finance at Islamic banks in Panyabungan District.